Mind the Gaps in Tumor Immunity: Impact of Connexin-Mediated Intercellular Connections - Gleisner, María Alejandra; Navarrete, Mariela; Hofmann, Francisca; Salazar-Onfray, Flavio; Tittarelli, Andrés (Frontiers in Immunology, 2017)
Gap junctions-mediated intercellular communications (GJICs) are connexin (Cx)-formed plasma membrane channels that allow for the passage of small molecules between adjacent cells, and are involved in several physiopathological processes, including immune responses against cancer. In general, tumor cells are poorly coupled through GJs, mainly due to low Cx expression or reduced channel activity, suggesting that Cxs may have tumor suppressor roles. However, more recent data indicate that Cxs and/or GJICs may also in some cases promote tumor progression. This dual role of Cx channels in tumor outcome may be due, at least partially, to the fact that GJs not only interconnect cells from the same type, such as cancer cells, but also promote the intercellular communication of tumor cells with different types of cells from their microenvironment, and such diverse intercellular interactions have distinctive impact on tumor development. For example, whereas GJ-mediated interactions among tumor cells and microglia have been implicated in promotion of tumor growth, tumor cells delivery to dendritic cells of antigenic peptides through GJs have been associated to enhanced immune-mediated tumor elimination. In this review, we provide an updated overview on the role of GJICs in tumor immunity, focusing on the pro-tumor and anti-tumor effect of GJs occurring among tumor and immune cells. Accumulated data suggest that GJICs may act as tumor suppressors or enhancers depending on whether tumor cells interact predominantly with anti-tumor immune cells or with stromal cells. The complex modulation of immune-tumor cell GJICs should be taken into consideration in order to potentiate current cancer immunotherapies.